Indonesian students’ entrepreneurial behavior: The effect of creativity, passion, alertness and intention - Oktavio, Adrie; Mitasari, Rean; Sinarta, Yeyen; Kusumawidjaya, Erris; Wijaya, Verina; Widyawati, Christy (Journal of Eastern European and Central Asian Research (JEECAR), 2023)
The decision process that supports individual entrepreneurial conduct remains a fascinating problem. Besides, the current situation shows that many Indonesian universities have begun to include entrepreneurship as a required subject for their students. This study aimed to develop an entrepreneurial model to explain the formation of entrepreneurial behavior, focusing on students' roles of creativity, passion, alertness, and entrepreneurial intention. The sample consists of 411 final-year bachelor's students from Indonesian universities. The collected data was analyzed using General Structured Component Analysis (GSCA), and the results showed that all hypotheses could be adopted according to the data processing results. As for the core of entrepreneurship, entrepreneurial intention becomes a substantial predictor of entrepreneurial behavior. The findings of this study can undoubtedly contribute to the validation of earlier research findings. However, the few numbers of sample size and self-reported data might limit the generalizability of this study’s results.